The hydrothermal process of aeolian sand and its thermal effect on permafrost in Qinghai-Tibetan Plateau considering rainfall and evaporation under climate warming - Lan, Tianli; Ma, Qinguo; Xia, Huxi; Luo, Xiaoxiao (Frontiers in Environmental Science, 2022)
As the heat exchange interface between atmosphere and permafrost, land cover regulates the influence of climate warming on permafrost. With the development of desertification on the Qinghai-Tibetan Plateau (QTP), aeolian sand has emerged as a significant environmental factor influencing the hydrothermal process of permafrost. To reveal the hydro-thermal process within aeolian sand layer and the thermal effect of sand layer on permafrost in the QTP, a coupled hydro-thermo-vapor model considering rainfall and evaporation was established, and the long-term hydrothermal variation of stratum covered by aeolian sand were analyzed. The results show that: 1) Aeolian sand layer is conducive to alleviating permafrost degradation. The alleviation effect is related to the thickness of sand layer. 2) Water redistribution in sand layer and water accumulation in stratum are connected to thickness of sand layer. For the thin sand layer, the water content is low and remains unchanged in different years. The thick sand layer, acting as a permeability diode, makes the degree of water accumulation in sand layer considerable and the water storage of the stratum increase continuously. 3) When the sand layer becomes thicker, the increment of the equivalent thermal conductivity in cold season is larger than that in warm season, which will lead to the decrease of annual conductive heat. 4) In thin sand layer, heat convection and heat conduction are relatively small in the early stage, and heat conduction is the primary mode in the long term. In thick sand layer, heat transfer is dominated by heat convection and heat conduction in the early stage, but it is primarily reliant on heat convection in the long term.